THE IMAGE OF A WOMAN IN THE LITERATURE OF DIFFERENT ERAS - Саттарова Фируза Улугбековна (Web of Journals Publishing, 2024)
The article examines the types of female images and stereotypes of their behavior, as well as the peculiarity of the nature of women in Russian literature. The article is devoted to the study of the specifics of the types of female images and their social role in world literature and to trace how the image of a woman in Russian literature has changed over the centuries.
Keywords: charming, source of inspiration, fiery soul, image of the goddess, totem, cynicism, femininity.